THE INFLUENCE OF HOMO IPHONE ON TRENDS, LIFESTYLE AND BUYING DECISIONS IN CASE STUDY ON GEN Z - Peptiana; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This article is a literature study that aims to understand the influence of